Chapter 13 Making Sense of Cheshire West - Series, Lucy (Hart Publishing, 2020)
In 2014 the UK Supreme Court was asked to rule on whether three people with intellectual disabilities were deprived of their liberty. Each of these people were living in 'post-carceral' care settings in the community: a small care home, supported living and in foster care. The Supreme Court ruled that they were, and the resultant 'acid test' of deprivation of liberty under UK law means that over 300,000 people living in the community are considered to be detained and requiring legal safeguards. This This chapter analyses the ruling in its historical context and in light of the UN Convention on the Rights of Persons with Disabilities. It suggests future avenues for addressing some of the judgment's more paradoxical and troubling consequences.